HUBUNGAN IMPLEMENTASI KURIKULUM 2013 DENGAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR KABUPATEN BARITO KUALA - Tati'ah, Tati'ah; Oktaviya, Kiki Celvi (Elementary School Teacher Education of STKIP Al Hikmah Surabaya, 2019)
The purpose of this study was to determine the relationship between the implementation of the 2013 curriculum and the character education of the fifth grade students of Danda Jaya 2 Public Elementary School in Rantau Badauh Subdistrict, Barito Kuala Regency. The population in this study were all fifth grade students of Danda Jaya 2 Elementary School in Rantau Badauh District, Barito Kuala District which amounted to 30 students, the research method used was quantitative descriptive method. The data digger used is a questionnaire as the main data digging tool to collect data about the relationship of the implementation of the 2013 curriculum with student character education, and added documentation as a supporting data digging tool. Processing data uses the produc moment correlation formula and the results show that there is a relationship between curriculum implementation 2013 with character education of the fifth grade students of Danda Jaya State Elementary School 2, Rantau Badauh Subdistrict, Barito Kuala Regency, this was indicated by the value of r count = 0.951> rtable = 0.361 at a significant level of 5% with N = 30. ) states that there is a relationship between the implementation of the 2013 curriculum and the character education of the fifth grade students of Danda Jaya State Elementary School 2, Rantau Badauh Subdistrict, Barito Kuala District. It is stated that the results of the research are suggested to teachers to instill character values ??in each theme. lessons and teachers should be able to give good examples of character to their students.